A comparison of three methods of determination of energy density of elite figure skaters - Ziegler, P. J.; Nelson, J. A.; Tay, C.; Bruemmer, B.; Drewnowski, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2005)
Dietary energy density (kcal/g) is defined as available dietary energy per unit weight or volume of food. The consumption of energy-dense foods has been associated with increased obesity risk and with excessive weight gain. The objectives of this study were to compare how dietary energy density, calculated using three different methods relates to food choices and nutrient composition of the diets of elite figure skaters. Participants were 159 elite figure skaters attending training camps. Mean age was 18.4 y for boys (n = 79) and 15.9 y for girls (n = 80). Heights and weights were measured to calculate body-mass indices (BMI). Dietary intakes were based on 3-d food records analyzed using the Nutritionist IV program. Mean energy intakes were 2326 kcal/d for boys and 1545 kcal/d for girls. Dietary energy density, based on foods and caloric beverages only, was 1.0 kcal/g. Dietary ED was positively associated with percent energy from fat and negatively with percent energy from sugar. The main sources of dietary energy in this group were baked goods, cereals, regular soda, low-fat milk, fruit juices, bagels and pizza. Percent energy from fast foods was associated with higher dietary energy density, whereas percent energy from dairy products, soft drinks, vegetables, and fruit was associated with lower dietary energy density. These results are consistent with past observations; higher energy density diets were higher in fat. In contrast, there was a negative relationship between sugar content and energy density of the diet.